Domestic Wastewater Treatment with Multi Soil Layering Method with Variations of Hydraulic Loading Rate (HLT) And Organic Materials at Anaerobic Conditions. Issue 1 (1st December 2022) - Zubair, A; Ibrahim, R; Mangarengi, N A P; Yuswanda, T D B; Abdullah, N O
Abstract: Domestic wastewater is the largest producer of wastewater in Indonesia which comes from the remnants of household activities. Hazardous substances such as Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), Oil and Fat contained in wastewater can cause health problems for humans. In this study, domestic waste treatment was carried out using the Multi Soil Layering (MSL) method. The MSL system is a wastewater treatment method that utilizes the ability of soil as the main medium and several other media such as zeolite, gravel, charcoal, and sawdust which are formed in a multilevel brick pattern. The independent variables are the variation of soil mixture with sawdust (M1) and soil mixture with charcoal (M2) and also variations of Hydraulic Loading Rate namely HLR 500 L/m2.day (H1), 750 L/m 2 .day (H2), 1000 L/m 2 .day (H3). The characteristics of domestic wastewater include pH 6, BOD 236 mg/L, COD 514 mg/L, TSS 114 mg/L, Oil and Fat 8200 mg/L. The results showed that the best variation in the removal of pollutant levels was a mixture of soil with charcoal (M2) and HLR 500 L/m 2 .day (H1), with the average efficiency in reducing BOD, COD, TSS, Oil & Fat levels, respectively. 86.39%, 78.29%, 86.56% and 79.60%.